2021
DOI: 10.3390/molecules26082264
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of Apis mellifera Venom with a Synergistic Potential of Its Two Main Components—Melittin and PLA2—On Colon Cancer HCT116 Cell Lines

Abstract: Colon carcinogenesis is ranked second globally among human diseases after cardiovascular failures. Bee venom (BV) has been shown to possess in vitro anticancer effects against several types of cancer cells. The two main biopeptides of Apis mellifera BV, namely, melittin (MEL) and phospholipase A2 (PLA2), are suspected to be the biomolecules responsible for the anticancer activity. The present work aims to evaluate the cytotoxic effect of the A. mellifera venom on human colon carcinoma cells (HCT116), and to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Altogether, these findings confirm the cytotoxic effect of A. mellifera syriaca venom on HeLa cancer cells in vitro. Additionally, the results support the hypothesis of our previous work, which suggests the importance of MEL in conferring the BV’s anticancer properties [ 23 ]. Moreover, by comparing the EC 50 values of BV, MEL, and Bv-PLA2 with those of our previous work on human colon cancer cells [ 23 ], we found that MEL is more effective on human colon cancer cells (EC 50 = 14.05 µg/mL) than on HeLa cells (EC 50 = 19.7 µg/mL).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Altogether, these findings confirm the cytotoxic effect of A. mellifera syriaca venom on HeLa cancer cells in vitro. Additionally, the results support the hypothesis of our previous work, which suggests the importance of MEL in conferring the BV’s anticancer properties [ 23 ]. Moreover, by comparing the EC 50 values of BV, MEL, and Bv-PLA2 with those of our previous work on human colon cancer cells [ 23 ], we found that MEL is more effective on human colon cancer cells (EC 50 = 14.05 µg/mL) than on HeLa cells (EC 50 = 19.7 µg/mL).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, the results support the hypothesis of our previous work, which suggests the importance of MEL in conferring the BV’s anticancer properties [ 23 ]. Moreover, by comparing the EC 50 values of BV, MEL, and Bv-PLA2 with those of our previous work on human colon cancer cells [ 23 ], we found that MEL is more effective on human colon cancer cells (EC 50 = 14.05 µg/mL) than on HeLa cells (EC 50 = 19.7 µg/mL). In contrast, BV and Bv-PLA2 did not show a significant difference between the two types of cancer cells.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations